Développement et formation communautaire: les Ganawuri du Nigeria - Berthoud, Gerald (Anthropologica, 2022)
This article explores the history of the Ganawuri in the 20th century in order to show how the communal formation of the precolonial period influences the secondary ethnic formation which characterizes their present condition and explains the resistance of the Ganawuri to an economic development based on inequality.